2000
DOI: 10.1146/annurev.arplant.51.1.49
|View full text |Cite
|
Sign up to set email alerts
|

SUGAR-INDUCED SIGNAL TRANSDUCTION IN PLANTS

Abstract: s Abstract Sugars have important signaling functions throughout all stages of the plant's life cycle. This review presents our current understanding of the different mechanisms of sugar sensing and sugar-induced signal transduction, including the experimental approaches used. In plants separate sensing systems are present for hexose and sucrose. Hexokinase-dependent and -independent hexose sensing systems can further be distinguished. There has been progress in understanding the signal transduction cascade by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(112 citation statements)
references
References 189 publications
1
95
0
3
Order By: Relevance
“…The greater accumulation of starch in leaves transferred from LL to HL relative to that found in HL-acclimated leaves suggests a more limiting carbon export capacity in pumpkin (and perhaps V. phoeniceum), whereas excess starch accumulation was not observed in the apoplastic loaders pea and spinach. Down-regulation of photosynthesis is a common response when the synthesis of sugars far exceeds their export and utilization (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Such repression of photosynthesis would be expected to impact photosynthetic capacity, as was consistently observed for both symplastic loaders compared with the apoplastic loaders in the present study.…”
Section: Photosynthetic Acclimation In the Symplastic Loaders Pumpkinsupporting
confidence: 71%
“…The greater accumulation of starch in leaves transferred from LL to HL relative to that found in HL-acclimated leaves suggests a more limiting carbon export capacity in pumpkin (and perhaps V. phoeniceum), whereas excess starch accumulation was not observed in the apoplastic loaders pea and spinach. Down-regulation of photosynthesis is a common response when the synthesis of sugars far exceeds their export and utilization (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Such repression of photosynthesis would be expected to impact photosynthetic capacity, as was consistently observed for both symplastic loaders compared with the apoplastic loaders in the present study.…”
Section: Photosynthetic Acclimation In the Symplastic Loaders Pumpkinsupporting
confidence: 71%
“…More recent studies in potato tubers revealed that sucrose and glucose lead to redox activation of AGPase via two different signaling pathways involving SNF1-related protein kinase (SnRK1) and hexokinase, respectively (16). Hexokinase and SnRK1 are both implicated in a regulatory network that controls the expression and phosphorylation of cytosolic enzymes in response to sugars (17). How they are linked to reductive activation of AGPase and starch synthesis in the plastid remains unresolved.…”
mentioning
confidence: 99%
“…Transformants were screened for resistance to the herbicide Basta TM . For analysis of GUS activity, tissue samples of T2 transformants were treated with GUS staining buffer (100 mM Na 2 HPO 4 /NaH 2 PO 4 ), pH 7.0, 10 mM Na 2 EDTA, 0.5 mM K 3 [Fe(CN)6], 0.5 mM K 4 [Fe(CN) 6 ], and 0.08% X-GlcA (Duchefa, Haarlem, The Netherlands) for 20 h at 37°C. Green tissues were bleached with ethanol before examination.…”
Section: Generation Of Promoter::gus Plantsmentioning
confidence: 99%
“…Acid invertases are responsible for sucrose unloading from the conducting tissues and for the adjustment of the hexose/sucrose ratio, which affects plant development including programmed cell death [3]. Thus, the hexose/sucrose ratio acts as an important metabolic signal, which dramatically affects gene expression profiles [4][5][6][7][8]. Consequently, the expression patterns of CWI and VI have to be tightly controlled, both temporally and spatially.…”
Section: Introductionmentioning
confidence: 99%